ANALISIS SOSIAL EKONOMI MASYARAKAT PERAMBAH DI KAWASAN TAMAN HUTAN RAYA NIPA-NIPA KOTA KENDARI - nur Arafah; Hafidah Nur; Narni Narni (Universitas Haluoleo, 2015)
This research aims to know the level of forest encroachment impacts at Nipa Nipa forest toward the socio-economic condition of the community araound the forest. The result of this shows that the deforestation has caused great biodiversity lost and residence expansion around the forest while the wide of area that has been converted in Puunggaloba area for farming and hausingare 4,42 hectare. The numbers of family who actively take adventages from the forest are 221 families. The encroachment activities commited by the respondent has a positive relationship with socio-economic of the community but have no relationship with ( not significant effect) all the socio-economic variable of community who live in Puncak Puunggaloba area. As suggested, there should be a follow up research on socio-economic analysis of community who live around the forest as the source of information for local governent to improve their community welfare while saving the Nipa-Nipa forest Park Key word: Socio-Economic, Encroachment and Nipa Nipa Forest Park